2010
DOI: 10.1097/01.aoa.0000389626.41532.84
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for Awake Fiberoptic Intubation in a Parturient With Spinal Muscular Atrophy Type III for Cesarean Delivery

Abstract: S pinal muscular atrophy (SMA), an inherited motor neuron disease, causes progressive degeneration of the spinal cord anterior horn cells and leads to muscle atrophy, respiratory muscle insufficiency, and scoliosis. Although the disease is rare in parturients, when present, it causes multiple problems, including airway difficulties, respiratory compromise, and spinal abnormalities. Dexmedetomidine has been used to facilitate awake fiberoptic intubation but the effect of the drug in parturients is less known. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 0 publications
2
22
0
6
Order By: Relevance
“…Previous studies have also shown that intravenous dexmedetomidine has no adverse effect on parturients and neonates, [31][32][33] similar results were also obtained in the present study. The results showed no difference in the Apgar score, heart rate or NACS compared with the control group.…”
Section: )supporting
confidence: 92%
“…Previous studies have also shown that intravenous dexmedetomidine has no adverse effect on parturients and neonates, [31][32][33] similar results were also obtained in the present study. The results showed no difference in the Apgar score, heart rate or NACS compared with the control group.…”
Section: )supporting
confidence: 92%
“…[32][33][34][35] Recently, many studies have demonstrated that intrathecal ropivacaine or bupivacaine-dexmedetomidine may increase the duration and efficacy of analgesia and decrease postoperative analgesic use, without notable adverse effects. 11,12,36) The use of dexmedetomidine as an adjuvant to bupivacaine for covering Cesarean delivery provided better intra-operative analgesia and did not affect Apgar scores or caused any noticeable side effects. 13,28) The intrathecal doses of dexmedetomidine used in our study were based on previous human studies wherein no neurotoxic effects were documented at these doses.…”
Section: Discussionmentioning
confidence: 99%
“…dexmedetomidine to facilitate Cesarean delivery in the parturient population has been reported in several case reports, including in a woman with primary pulmonary hypertension, 10) and in another with spinal muscular atrophy. 11) On the contrary, many studies showed that dexmedetomidine was an effective adjuvant to intrathecal local anesthetics for prolonging the duration of analgesia for lower abdominal surgeries, lower limb surgeries and Cesarean delivery. 12,13) However, the preventive effect of intrathecal dexmedetomidine on shivering has not been evaluated.…”
mentioning
confidence: 99%
“…The antisialagogue and moderate analgesic properties of dexmedetomidine have been cited as other advantages. 41,42 We identified 19 articles, five RCTs 13,29,43-45 and 14 case reports and case series [46][47][48][49][50][51][52][53][54][55][56][57][58][59] describing the use of dexmedetomidine for AFOI, usually as the sole agent but occasionally in combination with midazolam 43 or ketamine. 60 Although a TCI system for dexmedetomidine has been described for awake intubation, 47 it is generally administered as a slow bolus (usually 1 lgÁkg -1 over 10-20 min) to avoid peak-dose hypertension (which may exacerbate a bradycardia-related fall in cardiac output) followed by an infusion (usually of 0.1-0.7 lgÁkg…”
Section: Dexmedetomidinementioning
confidence: 99%
“…51 The safe respiratory profile of dexmedetomidine has been borne out by reports describing its use in patients with raised intracranial pressure at risk from hypoventilation 52 and in obstetrics with minimal adverse neonatal sequelae. 53,54 The ability to produce a deeply sedated state while maintaining a safe degree of respiratory function has also allowed it to be successfully used in children and uncooperative adults. 55,56 Nevertheless, the real advantage of a sedative that spares respiratory function may become apparent when the clinician is presented with patients already in or at risk of airway obstruction and/or respiratory failure; yet (not surprisingly), to date, there have been only limited case series dealing with such cases.…”
mentioning
confidence: 99%